2004
DOI: 10.1023/b:emas.0000031723.62736.24
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Effects of Crude Oil Pollution on Soil Properties, Germination and Growth of Maize (Zea Mays) using Two Crude Types – Forcados Light and Escravos Light

Abstract: The effect of crude oil pollution on soil properties, germination and height of maize (Zea mays) was investigated under natural environment in three separate pot experiments. Two crude oil types--Forcados light and Escravos light were used. In Experiment 1, the effect of crude oil application on germination using high pollution levels of 5, 15, 25 and 40 mL kg(-1) of soil was assessed. In Experiment 2, the effect of crude oil application on maize plant height using the same pollution levels was assessed. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 8 publications
7
38
0
Order By: Relevance
“…The percentage soil organic carbon content of the soil samples increased with increase in the concentration of the PHCs (SEO, BIT and CRO) applied at two months of incubation. The increase in the SOC content recorded in this experiment is consistent with earlier findings [4,15,18,19] and may be as a result of the microbial mineralization of the petroleum hydrocarbon compounds. Available N and P of the soil increased due to the contamination with petroleum hydrocarbon compounds, which contradicted the report of Onuh et al [18] who observed decreases as the level of crude oil pollution increased.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The percentage soil organic carbon content of the soil samples increased with increase in the concentration of the PHCs (SEO, BIT and CRO) applied at two months of incubation. The increase in the SOC content recorded in this experiment is consistent with earlier findings [4,15,18,19] and may be as a result of the microbial mineralization of the petroleum hydrocarbon compounds. Available N and P of the soil increased due to the contamination with petroleum hydrocarbon compounds, which contradicted the report of Onuh et al [18] who observed decreases as the level of crude oil pollution increased.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have been carried out on the effects of crude oil pollution on seed germination, plants and soil. For example, Ogboghodo et al [4] reported that crude oil inhibited the germination and growth of maize at high pollution levels while the growth of okro and fluted pumpkin seedlings were highly reduced with an increase in crude oil concentrations [5]. The response of plants to oil contamination depends upon the level of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…When crude oil spills on soil the condition of the soil becomes unsatisfactory for plants, because there is insufficient aeration due to a decrease in the air filled pore space (Degong, 1990;Kostreba, 1999;Ufot and Akande, 2005). It leads to alteration of the physical and chemical properties of the soil such as structure, hydraulic conductivity, exchangeable cations and pH (Ogboghodo et al, 2001). Odu (1981) reiterated that oil pollution has less effect on soil physical properties than in chemical properties.…”
Section: E-mail: Nwekson@hotmailcom Author(s) Agree That This Articlmentioning
confidence: 99%
“…The decrease in germination as diesel concentration increased might not just be due to the contaminant concentration but also to the hydrocarbon type, plant species and reduction in oxygen transfer between the seed and the surrounding environment (Salanitro et al, 2004). The negative effect of diesel oil on germination with increased diesel oil concentration might also be due to their hydrophobic properties as reported by Adam and Duncan (2002) and Ogboghodo et al (2004). Hydrocarbons may coat the seed, preventing or reducing gas and water exchange; they may also enter the seeds and alter the metabolic reactions and/or kill the embryo by direct toxicity (Adam and Duncan, 2002;Labud et al, 2007).…”
Section: Resultsmentioning
confidence: 94%